Effect of ulinastatin combined with mild therapeutic hypothermia on intestinal barrier dysfunction following cardiopulmonary resuscitation in rats - Zhang, Fang-Jie (Exp Ther Med, 2019)
The aim of the present study was to investigate the effect of ulinastatin (UTI) alone or combined with mild therapeutic hypothermia (MTH) on intestinal barrier dysfunction following cardiopulmonary resuscitation (CPR) in rats. A total of 25 adult male Sprague-Dawley rats were randomly organized into five groups: Sham; control; UTI; MTH; and the combined group. The latter four groups were induced with the asphyxiated cardiac arrest rat model and treated with different interventions. After 6 h of treatment, the intestinal tissues of the rats were examined by electron microscopy, and the levels of intestinal malondialdehyde (MDA) and superoxide dismutase (SOD) were determined. The results of the present study indicated that the target temperature had successfully been attained in MTH and the combined group, and the other three groups of rats all survived at a normal temperature. In the rats treated with UTI or MTH, the epithelial cells exhibited pathological changes in their tight junctions and epithelial cell surface microvilli compared with the sham group. In the rats treated with a combination of UTI and MTH, whilst the epithelial cells exhibited a few slight changes, including mitochondrial edema, they were largely similar to the normal epithelial cells. However, there were significant differences in the levels of MDA and SOD between the different treatment groups. UTI combined with MTH may serve a protective role by suppressing oxidative stress in the small intestinal mucosa following CPR in rats compared with either UTI or MTH treatment alone.